Creating novel medical diagnostics with a design for manufacturing. (17th April 2018) - Kumar, Ashok A
Abstract: When research is undertaken with the aim of creating a product to address real-world problems, incorporating considerations for manufacturing early in the creative process is important to reduce the barriers to translation later in development. A general description of the product development process is provided within the context of design for manufacturing. Building technologies on existing infrastructure for manufacturing can dramatically reduce the cost and time to create a product. The trade off of such an approach is that the work may not be deemed novel and may, thus, be harder to publish. A brief overview of recent work by several groups to develop a point-of-care test for Zika virus illustrates the repercussions of different approaches to novelty versus manufacturability. Actionable guidance is given for both researchers and those that support the research endeavor, such as funders and editors of peer-reviewed journals, on how to incorporate manufacturing into early research.